О морфологических и биологических особенностях белоглазки из верхнего Днестра - Опалатенко, Л.К. (Вестник зоологии, 1967)
Abramis sapa — not a numerous species of the Dniester ichthyofauna — is very simi-lar to the typical form of Abramis sapa (Pa 11.) as to the colour and measuring characters. Abramis sapa is distributed in the main channel of the Dniester and in the foothill tributaries. Abramis sapa grows intensively and reaches 21.4 cm when four years old. An average fertility of twenty females of four years old is equal to 14 thousands of roe-corns. In order to increase the number of Abramis sapa in the upper Dniester it is neces-sary to abolish the contamination of the Dniester with the sewage of the industrial enterprises.